Procedural and Substantive Dimensions of Human Rights Protection in the Judgment of Verein KlimaSeniorinnen v. Switzerland - Fauzi, Nisrina Putri (Fakultas Hukum Universitas Islam Jakarta, 2025)
Climate change not only impacts environmental damage, but also threatens the fulfillment of human rights. This phenomenon has given rise to various climate litigation cases that highlight the responsibility of states in protecting these rights. This study analyzes the Verein KlimaSeniorinnen v. Switzerland, which will be issued by the European Court of Human Rights (ECtHR) in 2024, emphasizes the procedural and substantive dimensions of human rights protection, especially related to the court's new paradigm of the applicant's legal standing and the affirmation of the state's positive obligation to mitigate the impact of climate change. This study uses a juridical-normative method with a legislative and case approach. The results of the study show that procedurally, ECtHR expands the meaning of locus standi by recognizing associations as parties with legal standing to represent groups affected by climate change. Substantively, the court affirmed the positive obligation of the state to establish and implement effective climate mitigation policies to protect the rights of citizens. In conclusion, this ruling marks the evolution of the paradigm of human rights protection in the context of climate change. Therefore, the KlimaSeniorinnen ruling sets an important precedent for national and international courts in building an adaptive and responsive legal interpretation to the challenges of the climate crisis.